A voltage-controlled ring oscillator based on an FGMOS transistor. (August 2017) - Sharroush, Sherif M.
Abstract: This paper can be divided into two parts. The first part contains a comprehensive survey on the applications of voltage-controlled oscillators and the innovations in their designs. The second part presents a voltage-controlled ring oscillator (VCRO) based on using a floating-gate metal-oxide semiconductor (FGMOS) transistor in its delay element. According to this VCRO, there are no extra elements; instead, the control behavior is included in the delay element itself. The presented VCRO is analyzed quantitatively with the expressions of the oscillation frequency in terms of the control voltage and the average power consumption derived. The presented VCRO has a good linearity over the full range from 0 V to the power-supply voltage and doesn't suffer from the need to turn on the MOS transistor. The effects of the process, voltage, and temperature (PVT) variations and the technology scaling on the performance of this VCRO are also investigated. The performance of the presented VCRO is compared with that of other schemes by simulation adopting the Berkeley predictive technology model (BPTM) of the 45 nm CMOS technology with a power-supply voltage, V DD, equal to 1 V.